High-Yield Production of 4-Hydroxybenzoate From Glucose or Glycerol by an Engineered Pseudomonas taiwanensis VLB120 - Lenzen, Christoph; Wynands, Benedikt; Otto, Maike; Bolzenius, Johanna; Mennicken, Philip; Blank, Lars M.; Wierckx, Nick (Frontiers in Bioengineering and Biotechnology, 2019)
Aromatic compounds such as 4-hydroxybenzoic acid are broadly applied in industry for a myriad of applications used in everyday life. However, their industrial production currently relies heavily on fossil resources and involves environmentally unfriendly production conditions, thus creating the need for more sustainable biotechnological alternatives. In this study, synthetic biology was applied to metabolically engineer Pseudomonas taiwanensis VLB120 to produce 4-hydroxybenzoate from glucose or glycerol as sole carbon sources. Genes encoding a 4-hydroxybenzoate production pathway were integrated into the host genome and the flux towards the central precursor L-tyrosine was enhanced by overexpressing genes encoding key enzymes of the shikimate pathway. The flux towards tryptophan biosynthesis was decreased by introducing a P290S point mutation in the trpE gene, and degradation pathways for 4-hydroxybenzoate, 4-hydroxyphenylpyruvate and 3-dehydroshikimate were knocked out. The resulting production strains were tailored for the utilization of different substrates through the rational modification of central carbon metabolism. In batch cultivations with mineral medium containing 20 mM glucose, the best strain produced 3.3 mM 4-hydroxybenzoate with a C-mol yield of 19.0%. Using 40 mM glycerol as a sole carbon source, the concentration increased to 5.1 mM 4-hydroxybenzoate with a C-mol yield of 29.6%. In all, the highly efficient conversion of bio-based substrates into 4-hydroxybenzoate by these deeply engineered P. taiwanensis strains brings the renewable production of aromatics one step closer.